Do I know as much as I think I do? - Plohl, Nejc (Psihološka obzorja (Ljubljana), 2018)
Realistic perception of our own knowledge is important in various areas of everyday life, yet previous studies reveal that our self-perception is full of shortcomings. The present study focused on general overestimation of knowledge and differences between experts and the less-skilled (The Dunning-Kruger effect), self-perceived knowledge of non-existing concepts (overclaiming), and the illusion of knowledge. These phenomena were tested with an instrument which measured the actual knowledge of different domains (grammar, literature, and nanotechnology), as well as self-assessed knowledge. Results showed that, on average, participants overestimated their absolute performance, but not their performance relative to others. Furthermore, the bottom quartile overestimated their absolute and their relative performance most, while the top quartile perceived their absolute performance most accurately and substantially underestimated their relative performance. Results related to overclaiming showed that 56% of respondents claimed knowledge of at least one non-existent book and that the extent of overclaiming was substantially correlated with self-perceived expertise. Lastly, results showed that an increased quantity of information about nanotechnology led to a false certainty in answering questions from this area.
Keywords: ability; assessment; cognition; cognitive bias; competence; decision making; Dunning-Kruger effect; Dunning-Krugerjev učinek; illusion of knowledge; iluzija znanja; judgement; knowledge; kognicija; kompetence; mišljenje; objectivity; objektivnost; ocenjevanje; odločanje; overclaiming; overestimation of knowledge; perception of knowledge; poznavanje neobstoječih konceptov; precenjevanje znanja; presojanje; pristranskost; samoocenjevanje; samopercepcija; self-perception; self-report; sposobnosti; subjectivity; subjektivnost; thinking; znanje